Maternal Vitamin D Sufficiency Is Associated with Lower Circulating TNF-α in Breastfeeding Infants. (29th May 2020) - Newton, Danforth; Baatz, John; Shary, Judy; Washington, Renee; Wagner, Carol
Abstract: Objectives: Exclusively breastfeeding (BrF) infants are at risk for vitD deficiency if they or their mothers are not supplemented. However, it is unknown if maternal or direct infant vitD supplementation could have differential effects on the BrF child. We hypothesized that maternal vitD status may affect concentrations of pro-inflammatory cytokines in infants. Methods: Exclusively BrF infants and mothers were enrolled in a clinical study in which infant vitD sufficiency was achieved by either direct supplementation with 400 IU/d vitD3 or mothers were supplemented with 6400 IU/d. Infant and maternal plasma 25-hydroxyvitamin D (25-D) values were determined by radioimmunoassay at enrollment (1-mo infant) and completion (5-mo). Concentrations of 10 pro-inflammatory cytokines in infant plasma were determined by electrochemiluminescence. ANOVA, t-tests and linear correlations were used to calculate relationships between vitD and circulating cytokines in 49 infant-mother pairs at study enrollment and 39 pairs at completion. Results: Plasma concentrations of 10 pro-inflammatory cytokines measured were very low (pg/ml range). Neither infant nor maternal vitD status (sufficiency defined as plasma 25-D > 30 ng/ml) were associated with 9 measured cytokines in infant blood (IFN-γ, IL-1b, –2, –4, –6, –8, –10, –12, –13). In contrast, concentrations of tumor necrosis factor (TNF)-α in infant plasma were inversely correlated to maternal vitD status ( r = −0.37; P  = 0.02 at study completion). At study enrollment, BrF infants of vitD-sufficient mothers had mean 20% lower plasma TNF-α concentration than infants of vitD-insufficient mothers ( P  = 0.02), regardless of the infant's own vitD status. VitD sufficiency in infants per se was associated with mean 5% lower plasma TNF-α concentration, non-significantly different to that of vitD-deficient infants. Conclusions: These results indicate that vitD-mediated changes in breastmilk composition can affect the immune system of BrF infants. Circulating concentrations of the major pro-inflammatory cytokine TNF-α were significantly lower in infants with vitD-sufficient mothers regardless of the infant's own vitD status. Studies are currently investigating vitD-associated effects on responses of BrF infants' immune cells to antigenic challenge. Funding Sources: NIH/NCATS, SC Translational Research Institute, MUSC Pediatrics.